Immune Surveillance of Unhealthy Cells by Natural Killer cells - Iannello, Alexandre (Cold Spring Harb Symp Quant Biol, 2013)
Pathogenic and oncogenic insults result in the induction of intrinsic defense mechanisms such as cell death pathways and senescence, and extrinsic pathways that mobilize immune responses to destroy unhealthy cells. Both protective mechanisms presumably evolved to limit the damage these insults could inflict on the host. After viral infection or malignant transformation, unhealthy cells can be directly sensed by natural killer (NK) and some T cells via the activating receptor NKG2D. All NK cells and subsets of T cells express NKG2D. The NKG2D/ligand system represents a major recognition mechanism for detection and elimination of unhealthy cells. Here we discuss different pathways, including stress pathways, that are responsible for cell surface display of ligands for NKG2D, which are self-proteins that are minimally expressed by normal cells. We also discuss new results indicating that efficient elimination of tumor cells that display NKG2D ligands depends on the recruitment of NK cells and other immune cells to the tumor, which can be regulated by distinct mechanisms, including the p53-dependent production of chemokines by senescent tumors. The cooperative effect of pathways that induce the display NKG2D ligands and distinct pathways that mobilize immune cells provides a higher degree of specificity to the NK cell response.